Determination of the number of J/ψ events with inclusive J/ψ decays *Supported by National Key Basic Research Program of China (2015CB856700), National Natural Science Foundation of China (NSFC) (10805053, 11125525, 11175188, 11235011, 11322544, 11335008, 11425524), Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program, the CAS Center for Excellence in Particle Physics (CCEPP), Collaborative Innovation Center for Particles and Interactions (CICPI), Joint Large-Scale Scientific Facility Funds of NSFC and CAS (11179007, U1232201, U1232107, U1332201), CAS (KJCX2-YW-N29, KJCX2-YW-N45), 100 Talents Program of CAS, INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology, German Research Foundation DFG (Collaborative Research Center CRC-1044), Istituto Nazionale di Fisica Nucleare, Italy; Ministry of Development of Turkey (DPT2006K-120470), Russian Foundation for Basic Research (14-07-91152), U. S. Department of Energy (DE-FG02-04ER41291, DE-FG02-05ER41374, DE-FG02-94ER40823, DESC0010118), U.S. National Science Foundation, University of Groningen (RuG) and the Helmholtzzentrum fuer Schwerionenforschung GmbH (GSI), Darmstadt; WCU Program of National Research Foundation of Korea (R32-2008-000-10155-0). (January 2017) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Ai 艾, X. C. 小聪; Albayrak, O.; Albrecht, M.; Ambrose, D. J.; Amoroso, A.; An 安, F. F. 芬芬; An 安, Q. 琪; Bai 白, J. Z. 景芝; Baldini Ferroli, R.; Ban 班, Y. 勇; et al.
Abstract: A measurement of the number of J/ψ events collected with the BESIII detector in 2009 and 2012 is performed using inclusive decays of the J/ψ. The number of J/ψ events taken in 2009 is recalculated to be (223.7 ± 1.4) × 10 6, which is in good agreement with the previous measurement, but with significantly improved precision due to improvements in the BESIII software. The number of J/ψ events taken in 2012 is determined to be (1086.9 ± 6.0) × 10 6 . In total, the number of J/ψ events collected with the BESIII detector is measured to be (1310.6 ± 7.0) × 10 6, where the uncertainty is dominated by systematic effects and the statistical uncertainty is negligible.